Functional Abdominal Pain Disorders in Children - Muzal Kadim (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Diagnostic criteria for functional abdominal pain has developed in the last decade, from the Rome III criteria to the Rome IV criteria. The major change was in the phrase "abdominal pain related gastrointestinal disorders" to "functional abdominal pain disorders (FAPD)". According to Rome IV criteria, FAPD  are divided into functional dyspepsia (FD), irritable bowel syndrome (IBS), abdominal migraine, and functional abdominal pain-not otherwise specified (FAP-NOS). In order to diagnose FAPD, it is important to pay attention to alarm signs that can indicate organic abnormalities. The pathophysiology of FAPD was a complex interaction between psychosocial, genetic, environmental and life experiences of children through the gut brain axis. The risk factors for functional abdominal pain in children include psychological factors including anxiety and depression, stress conditions, negative experiences, and socioeconomic status.